Laparoscopic Retroperitoneal Lymph Node Dissection for Stage I Nonseminomatous Germ Cell Testis Tumors: The First Case Series in Iran - Ziaee, Seyed Amir Mohsen; Tabibi, Ali; Sharifiaghdas, Farzaneh; Ghahestani, Seyyed Mohammad; Zare, Samad; Samzadeh, Mohammad (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: To report laparoscopic retroperitoneal lymph node dissection (RPLND) as an approach for management of low-stage nonseminomatous germ cell testis tumors (NSGCT). Materials and Methods: Between August 2002 and December 2008, 19 patients with stage I NSGCT underwent RPLND in our center. Results: Mean operation time was 340 minutes (range, 250 to 360 minutes). Procedure in 2 (10.5%) patients was converted to open. Four (21%) patients had tumors with pure histopathology while other 15 (79%) had mixed histopathology. The mean number of removed lymph nodes was 11 (range, 6 to 14). Pathology revealed lymph node involvement in 8 (42%) patients, including 6 (75%) viable tumors and 2 (25%) teratoma. After on average 47-month follow-up (range, 3 to 70 months), recurrence occurred in 2 (10.5%) patients, who underwent open retroperitoneal lymph node dissection after chemotherapy, and surgical pathology revealed teratoma in one and fibrotic tissue in another. No patient developed systematic metastasis during followup period. Conclusion: Our results show that compared with open surgery, RPLND has same oncologic outcome, but lower, and can be recommended for management of patients with low stage NSGCT.